Managing complexity in organizations : text and cases - Nedopil, Christoph; Steger, Ulrich; Amann, Wolfgang (Basingstoke, UK : Palgrave Macmillan, 2011)
Combining rigorous academic research with the latest practical tools and techniques this book explores the growing area of complexity management in business
Includes bibliographical references and index.
Keywords: Organizational change -- Case studies; Complex organizations -- Management -- Case studies